Fast light generation using GaAlAs/GaAs waveguide - Afroozeh, A.; Bahadoran, M.; Amiri, I. S.; Samavati, A. R.; Ali, J.; Yupapin, P. P. (My University, 2012)
Generation of fast light pulses through a nonlinear microring system is an attractive research challenge for high speed optical and quantum computer, optical communication networks and secured communication. In this paper generation of fast light through GaAlAs/GaAs waveguides with fabricated Micro Ring Resonator is reported. Using multistage system, the attosecond pulse can be generated. Simulation results obtained have shown that the generation of a very narrow full-width at half maximum (FWHM) line width and sharp tip is achieved. We propose a new system of multistage micro ring resonators consist of four rings for optical communication system. Here, pulse width of 15 attosecond can be obtained, using proper parameters of the proposed system. © Penerbit UTM Press, Universiti Teknologi Malaysia.
Keywords: Attosecond pulse; Microring resonator; Optical communication